CAXIAS DO SUL TECHNOLOGY INCUBATOR: TECHNOLOGICAL INNOVATION THROUGH THE TRIPLE HELIX - Tisott, Priscila Bresolin (2014)
The aim of this study was to identify how the Triple Helix concept is applied in the activities of the Caxias do Sul Society of Technology Incubation. To achieve this goal, semi-structured in-depth interviews were conducted at ITEC, the University of Caxias do Sul, Chamber of Industry, Commerce and Services of Caxias do Sul, Caxias do Sul City Hall and Comlink Electronic Equipments, one of the companies that was successfully incubated. Content analysis of the results showed that the agents act mainly through the provision of financial resources. Furthermore, the main benefits obtained by the University from this relationship are the returnon investment in the form of registered patents, attracting new students and recognition as a technological, entrepreneurial and innovative university. The perceived benefits for the industrial sector are training and development for businesses and entrepreneurs, while the municipal government perceives the reduced number of businesses failing and the financial returns, in the form of taxes, as benefits. The findings show that the Triple Helix concept developed by Etzkowitz (2009) plays a cooperative and participatory role in the Technology Incubator, even though it could be applied to more segments of society.